Plasmonic silicon Schottky photodetectors: The physics behind graphene enhanced internal photoemission - Levy, Uriel; Grajower, Meir; Gonçalves, P. A. D.; Mortensen, N. Asger; Khurgin, Jacob B. (APL photonics, 2017)
Recent experiments have shown that the plasmonic assisted internal photoemission from a metal to silicon can be significantly enhanced by introducing a monolayer of graphene between the two media. This is despite the limited absorption in a monolayer of undoped graphene ( ∼ π α = 2.3 % ). Here we propose a physical model where surface plasmon polaritons enhance the absorption in a single-layer graphene by enhancing the field along the interface. The relatively long relaxation time in graphene allows for multiple attempts for the carrier to overcome the Schottky barrier and penetrate into the semiconductor. Interface disorder is crucial to overcome the momentum mismatch in the internal photoemission process. Our results show that quantum efficiencies in the range of few tens of percent are obtainable under reasonable experimental assumptions. This insight may pave the way for the implementation of compact, high efficiency silicon based detectors for the telecom range and beyond.